The Expression Profiles of mRNAs and lncRNAs in Buffalo Muscle Stem Cells Driving Myogenic Differentiation - Zhang, Ruimen; Wang, Jinling; Xiao, Zhengzhong; Zou, Chaoxia; An, Qiang; Li, Hui; Zhou, Xiaoqing; Wu, Zhuyue; Shi, Deshun; Deng, Yanfei; Yang, Sufang; Wei, Yingming (Frontiers in Genetics, 2021)
Buffalo breeding has become an important branch of the beef cattle industry. Hence, it is of great significance to study buffalo meat production and meat quality. However, the expression profile of mRNA and lncRNA molecules in muscle stem cells (MuSCs) development in buffalo has not been explored fully. We, therefore, performed mRNA and lncRNA expression profiling analysis during the proliferation and differentiation phases of MuSCs in buffalo. The results showed that there were 4,820 differentially genes as well as 12,227 mRNAs, and 1,352 lncRNAs. The differentially expressed genes were shown to be enriched in essential biological processes such as cell cycle, p53 signaling pathway, RNA transport and calcium signaling pathway. We also identified a number of functionally important genes, such as MCMC4, SERDINE1, ISLR, LOC102394806 and LOC102403551, and found that interference with MYLPF expression significantly inhibited the differentiation of MuSCs. In conclusion, our research revealed the characterizes of mRNA and lncRNA expression in the differentiation of buffalo MuSCs. This study can be used as an important reference for the study of RNA regulation during muscle development in buffalo.